Whole genome sequence-based analysis of Staphylococcus aureus isolated from bovine mastitis in Thuringia, Germany - Moawad, Amira A.; El-Adawy, Hosny; Linde, Jörg; Jost, Ines; Tanja, Gärtner; Katja, Hruschka; Karsten, Donat; Neubauer, Heinrich; Monecke, Stefan; Tomaso, Herbert (Frontiers in Microbiology, 2023)
Background: Bovine mastitis is a common disease of dairy cattle causing major economic losses due to reduced yield and poor quality of milk worldwide. The current investigation aimed to gain insight into the genetic diversity, antimicrobial resistance profiles and virulence associated factors of Staphylococcus (S.) aureus isolated from clinical bovine mastitis in dairy farms in Thuringia, Germany.Methods: Forty Staphylococcus aureus isolates collected from clinical bovine mastitis cases from 17 Thuringian dairy farms were phenotyped and genetically characterized using whole genome sequencing.Results: Out of 40 S. aureus, 30 (75%) were confirmed as methicillin resistant isolates. The isolates showed elevated antimicrobial resistance against penicillin, tetracycline, and oxacillin, i.e., 77.5%, 77.5% and 75%, respectively. Lower resistance rates were found against moxifloxacin, ciprofloxacin, gentamicin and trimethoprim/sulfamethoxazole i.e. 35%, 35%, 30% and 22.5%, respectively. While resistance against clindamycin and erythromycin were rarely found (5% and 2.5%, respectively). All isolates were susceptible to linezolid, teicoplanin, vancomycin, tigecycline, fosfomycin, fusidic acid, and rifampicin. The isolates were assigned to five different sequence types: ST398 (n=31), ST1074 (n=4), ST504 (n=3), ST582 (CC15) (n=1) and ST479 (n=1).These isolates were also assigned to seven clusters with up to 100SNP which has facilitated geographical mapping and epidemiological distribution in Thuringia. Strains belonging to ST398 were classified into clusters 1, 2, 3, 4 and 7. The isolates of ST 504 were of cluster 5, those of ST1074 were belonging to cluster 6.Resistance genes blaZ, blaI, and blaR associated with penicillin resistance were found in 31 (80%) strains, all were belonging to ST398. Methicillin resistance associated mecA was identified in 30 (96.8%) isolates of ST398.All tetracycline and erythromycin resistant isolates were of ST398, and all harbored both tetM and ermA. About 90.3% of tetracycline resistant isolates assigned to ST398 were also carrying tetK gene..Sixty-eight virulence genes were identified among isolates. Both lukD/E and lukM/F-PV-P83 were identified in 22.5% of isolates.In this study, ST398 had the highest potential to cause disease and had a massive prevalence in bovine mastitis cases. Five different sequence types and seven clusters were identified in the federal state of Thuringia.